PENGARUH AKUNTABILITAS KEUANGAN, PENGAWASAN KEUANGAN DAERAH, DAN TRANSPARANSI ANGGARAN TERHADAP PENGELOLAAN KEUANGAN PEMERINTAH DAERAH KABUPATEN INDRAGIRI HULU - Gerryan Putra; M. Rasuli '; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of financial accountability, oversight, and transparency of the budget to the financial management of the district government indragiri upstream Regional Work Units in the District Indragiri Upstream Research conducted on 23 local work unit, which consists of 15 offices and 8 agencies located in Indragiri Hulu in 2016. Data collected from 44 respondents further data were analyzed with SPSS version 2.0 using descriptive statistical analysis and multiple linear regression analysis to generatetest classic assumptions, data analysis model, the coefficient of determination and prove the hypothesis. the results of this study showed no effect on the financial accountability of financial management, the H1 is rejected. While the t test toanswer the hypothesis 2 shows that there is a positive influence on the financial control of the area of the financial management with a significance of 0.002 at p <0.05. This shows that the area of financial supervision positive effect onfinancial management, this means that H2 is accepted. This means that if the supervision is good, controlled, and systematical, the financial management will be good too, while the t test to answer the hypothesis 3 shows that there is apositive effect of budget transparency on financial management with 0.000 significance at p <0.05. This shows that the positive effect on the budget transparency, financial management, this means the H3 is accepted.Keywords: financial accountability, supervision, transparency, management, and systematical